Motivation to Lead as Mediator of Relations Between the Dark Triad, Big Five, and Leadership Intention - Kennedy, Jeffrey C.; Chan, Kim Yin; Ho, Moon-Ho Ringo; Uy, Marilyn A.; Chernyshenko, Oleksander S. (Frontiers in Psychology, 2021)
This study seeks to enhance the distal-proximal modeling of personality trait–leader emergence relationships by (1) distinguishing between the motivation to lead (i.e., the reasons why a person seeks leadership roles) and leadership intention (i.e., one’s expressed desire to claim a leadership role) and by (2) examining how the Dark Triad traits add to the Big Five personality factors in predicting three motivation to lead factors and leadership intentions. Using personality and careers aspiration data collected from 750 university students, we found that affective-identity and social-normative motivation to lead mediate the effects of distal traits on intentions. In contrast, non-calculative motivation to lead does not contribute to leadership intentions, which has important implications for organizations seeking selfless leaders. Narcissism explains variance in leadership intentions over and above that explained by extraversion; this contrasts with the studies of leader emergence, where the effect of narcissism disappears once extraversion is controlled. Overall, our findings validate the three-factor conceptualization of motivation to lead and illuminate the roles of both bright and dark personality factors in understanding individual desire to attain leadership roles.